A domain decomposition approach for full-field measurements based identification of local elastic parameters. (1st March 2015) - Lubineau, Gilles; Moussawi, Ali; Xu, Jiangping; Gras, Renaud
Abstract: We propose a domain decomposition formalism specifically designed for the identification of local elastic parameters based on full-field measurements. This technique is made possible by a multi-scale implementation of the constitutive compatibility method. Contrary to classical approaches, the constitutive compatibility method resolves first some eigenmodes of the stress field over the structure rather than directly trying to recover the material properties. A two steps micro/macro reconstruction of the stress field is performed: a Dirichlet identification problem is solved first over every subdomain, the macroscopic equilibrium is then ensured between the subdomains in a second step. We apply the method to large linear elastic 2D identification problems to efficiently produce estimates of the material properties at a much lower computational cost than classical approaches.